A Proposed Cloud Computing Model For Supporting Academic Courses And it's Application In Future Academy (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
Dependence on Information Technology (IT) in universities has become inevitable. They use IT for both admin works, academic activities in the form of e-Education and for training on various software packages. In large universities, where they have thousands of students working on hundreds of computers, IT environment requires expensive infrastructure. Consequently, academic institutes tend to look for solutions to reduce the cost of computer services represented in computer process and hardware maintenance, software implementation, maintenance and upgrade cost. Cloud computers emerged as a possible solution, but the problem remained, "how to implement it?". This paper presents a proposed cloud computing implementation model to support academic courses. This model was implemented and tested in Future Academy Higher Education Institutions (FAHEI), one of the largest private sector education institutes in Egypt.